2022
DOI: 10.3389/fcvm.2022.999254
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics insights into potential mechanism of SGLT2 inhibitors cardiovascular benefit in diabetic cardiomyopathy

Abstract: BackgroundMetabolic and energy disorders are considered central to the etiology of diabetic cardiomyopathy (DCM). Sodium-glucose cotransporter-2 inhibitors (SGLT2i) can effectively reduce the risk of cardiovascular death and heart failure in patients with DCM. However, the underlying mechanism has not been elucidated.MethodsWe established a DCM rat model followed by treatment with empagliflozin (EMPA) for 12 weeks. Echocardiography, blood tests, histopathology, and transmission electron microscopy (TEM) were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…4 studies ( 12 , 24 , 27 , 45 ) reported weight loss. 7 studies ( 11 , 15 , 19 , 20 , 30 , 32 , 41 ) showed no differences in changes to body weight and 1 study ( 13 ) reported increases in body weight. Table 3 displayed the specific results.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…4 studies ( 12 , 24 , 27 , 45 ) reported weight loss. 7 studies ( 11 , 15 , 19 , 20 , 30 , 32 , 41 ) showed no differences in changes to body weight and 1 study ( 13 ) reported increases in body weight. Table 3 displayed the specific results.…”
Section: Resultsmentioning
confidence: 98%
“…The FA metabolism-related indicators in heart samples were as follows: the content of FA translocase (CD36), carnitine palmitoyl transferase-1 (CPT-1), peroxisome proliferator-activated receptor γ coactivator-1α (PGC1-α), peroxisome proliferator-activated receptor α (PPARα), the ratio of phosphorylated-adenosine monophosphate-activated protein kinase to adenosine monophosphate-activated protein kinase (p-AMPK/AMPK), the ratio of phosphorylated-acetyl CoA carboxylase to acetyl CoA carboxylase (p-ACC/ACC), myocardial TG content, myocardial FA uptake, epicardial fat volume, the total number of lipid droplets in cardiomyocytes, and proteomics and metabolomics of myocardial tissue (details were shown in Table 3 ). Among these, 6 studies showed that SGLT2i increased the FA metabolism of the heart ( 12 , 15 , 30 , 41 , 42 , 44 ), including the expressions of FA uptake-related transporter protein CD36, FA from cytoplasm into mitochondria related protein CPT-1, FA oxidation-related proteins (PGC1-α, PPARα, AMPK, and ACC); notably, the EF values of 5/6 studies ( 12 , 30 , 41 , 42 , 44 ) were >50% which were similar to the EF values of HFpEF. Cardiac FA metabolism was reduced in 1 study ( 13 ) and remained unchanged in 2 studies ( 11 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Multi-omics analysis showed that EMPA could regulate and partially restore the levels of multiple metabolites related to stress in cardiomyocytes under high glucose environment, alleviating lipid toxicity 34 . Enhanced diabetic cardiac fatty acid (FA) metabolism and perturbations in the biosynthesis of unsaturated fatty acid and arachidonic acid metabolism are potential drivers of the cardiovascular benefits of EMPA 35 . Animal experiments have also demonstrated that fatty acid oxidation is one of the targets of EMPA therapy in db/db mouse hearts 36 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies showing alterations in circulating metabolites including amino acids caused by treatment with an SGLT2i [32][33][34][35], but there have been no study focusing on BAIBA, a non-proteinogenic amino acid also known as 3-aminoisobutyric acid or 3-amino-2-methyproponic acid. In the present study, the proportion of patients in whom plasma BAIBA was detected was higher in patients receiving an SGLT2i than in patients not receiving an SGLT2i.…”
Section: Discussionmentioning
confidence: 99%